The Effect of Loan Performance on Profit Growth WITH Operational Costs and Operating Income (OCOI) as Intervening Variables at Commercial Banks in Indonesia - Pramukti, Eko; Laba, Abdul Rakhman; Pramukti, Andi Aswan (Economics and Business Journal (ECBIS), 2023)
This study aims to analyze and determine the effect of loan performance on profit growth with operational costs and operating income (OCOI) as intervening variables in commercial banks in Indonesia. The data analysis technique in this study uses Partial Least Square (PLS) using Smart PLS software. This data analysis technique is used to facilitate researchers in data processing and analysis. The results show that the loan performance coefficient positively and significantly affects profit growth. The results of testing loan performance on profit growth show a path coefficient of 0.372 with a t-statistic value of 3.504. The t-statistic value is smaller than the t-table value (1.96). The coefficient of operating costs and operating income shows a negative and significant impact on profit growth. The results of the OCOI test on profit growth show a path coefficient of -0.638 with a t-statistic value of 6.324. The t-statistic value is greater than the t-table value (1.96). The loan performance coefficient through operational costs and operating income is negative and not significant to profit growth. The results of testing the performance of loans through OCOI on profit growth show a path coefficient of -0.174 with a t-statistic value of 1.756. The t-statistic value is smaller than the t-table value (1.96).